FEAR AS A CATEGORY OF LANGUAGE OF POSTCOLONIALITY (ON FILMS BY WOJCIECH SMARZOWSKI: WESELE, DOM ZŁY, RÓŻA, DROGÓWKA) - Skórczewski, Dariusz (Porównania, 2015)
A most striking characteris-tic of Wojciech Smarzowski’s feature films is their uncanny atmosphere resulting from horrify-ing events and situations represented. This atmosphere seems to transgress the effect assumed in the genre to which the director refers, i.e. the thriller, and be rooted elsewhere than simply in the convention of classical horror cinema. Seeking an answer to the question concerning the causes of fear with which the spectatorship of The Wedding (Wesele), The Dark House (Dom zły), Rose (Róża), and Traffic Department (Drogówka), each of them so different from another, is confronted, the author attempts at theorizing the category of postcolonial fear. He offers the thesis that the fear evoked in Smarzowski’s movies is a medium for articulating the postcolonial trauma of memory of society engaged in dealing with its colonial past and present postcolonial realities. By articulating this trauma, the director carries out a peculiar work of memory in the “zone of tran-sition” (term borrowed from B. Buden).